Digital as the Future of Indonesia Economy Growth - Pandu Adi Cakranegara (Majalah Ilmiah Bijak, 2020)
Indonesia is a country that is currently in a developing country position. Indonesia was predicted to be one of the strongest economies in Asia, especially during the oil boom era where Indonesia has oil reserves that are driving economic growth. However, the presence of oil cannot be used for long-term investment and the consequences of the 1998 monetary crisis prevented Indonesia from reaching its potential. In the future the country's growth will be driven by technology. This research is applied research to use Porter's Competitive Advantage model for the State. The data used are secondary data from trusted institutions for which data is publicly available. The results of this study are that Indonesia has the opportunity to become a new economy power in the future as long as it can utilize the current momentum.